Representation of Nationalism Values in the Kadet 1947 Film (Semiotic Analysis of the Kadet 1947 Film) - Toyib Alwi Arahmad, Toyib Alwi Arahmad; Wirawanda, Yudha Wirawanda (Jogjakarta Communication Conference (JCC), 2023)
Film is a medium of communication as well as a medium for spreading messages, including messages of nationalism. The way to convey the message also varies, whether in the form of audio such as conversations or in the form of visuals such as sign. Nationalism is an idea formed to create freedom, lasting peace, and social justice in a country. In this research, the writer wants to examine the values of nationalism contained in the film Kadet 1947. The method used is descriptive qualitative with the aim of identifying, understanding, explaining and describing what happened. The purpose of this study is to find out the values of nationalism contained in the film of Kadet 1947. The results of the study show that in the Kadet 1947 film there are values of nationalism in accordance with the Budiawan concept of nationalism, namely the values of Patriotism, Willing to Sacrifice, Service to the Country, Sense of Owning, Pride on Country and Unity.